2006
DOI: 10.1097/01.hjh.0000251909.00923.22
|View full text |Cite
|
Sign up to set email alerts
|

AT1 receptor blockade is superior to conventional triple therapy in protecting against end-organ damage in Cyp1a1-Ren-2 transgenic rats with inducible hypertension

Abstract: Our findings indicate that hypertension in Cyp1a1-Ren-2 rats is a clearly angiotensin II-dependent model of hypertension with elevated circulating and tissue angiotensin II concentrations, and that antihypertensive treatment with AT1 receptor blockade is superior to conventional triple therapy in effective protection against hypertension-induced end-organ damage in this rat model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
67
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(75 citation statements)
references
References 34 publications
8
67
0
Order By: Relevance
“…Therefore, in the present study, Ang II and Ang(1-7) levels were determined in plasma and in nonclipped kidneys and hearts in separate experimental groups of the above-described mice (n = 8 in each group). At the end of the experiments (on day 26 after clip placement or sham operation), mice were sacrificed by decapitation, and plasma and tissue Ang II levels were assessed by radioimmunoassay (RIA) based on the procedure developed by Fox et al [30] and further modified and validated in our laboratory [4,5,14,27,[31][32][33] . This approach for blood and tissue sampling and Ang II assay, which is routinely used in our laboratory, allows us to compare the present results with those of our previous studies evaluating the role of RAS in the pathophysiology of hypertension [4,5,14,27,[31][32][33] .…”
Section: Series 3: Determinations Of Plasma and Kidney Tissue Ang II mentioning
confidence: 99%
“…Therefore, in the present study, Ang II and Ang(1-7) levels were determined in plasma and in nonclipped kidneys and hearts in separate experimental groups of the above-described mice (n = 8 in each group). At the end of the experiments (on day 26 after clip placement or sham operation), mice were sacrificed by decapitation, and plasma and tissue Ang II levels were assessed by radioimmunoassay (RIA) based on the procedure developed by Fox et al [30] and further modified and validated in our laboratory [4,5,14,27,[31][32][33] . This approach for blood and tissue sampling and Ang II assay, which is routinely used in our laboratory, allows us to compare the present results with those of our previous studies evaluating the role of RAS in the pathophysiology of hypertension [4,5,14,27,[31][32][33] .…”
Section: Series 3: Determinations Of Plasma and Kidney Tissue Ang II mentioning
confidence: 99%
“…Thus, we used total tissue ANG II levels as a reliable index of tissue RAS activity. The above described procedure for blood sampling and ANG II assay is routinely employed in our laboratory and this standardized approach allows us to compare the results from our previous studies evaluating the role of the RAS in the pathophysiology of hypertension [7,9,17,18,39] .…”
Section: Series 1: Assessment Of Systolic Bp Plasma and Kidney Ang Imentioning
confidence: 99%
“…In view of these previous observations that the largest amount of ANG II-like immunoreactivity on HPLC coeluted with ANG II and given the high specificity of the ANG II antisera [37] , the individual plasma and kidney samples obtained in the present study were not subjected to HPLC prior to the RIA. This methodological approach was validated by Mitchell et al [8] and since that time we have also employed this method routinely in our laboratory [7,9,17,18,39] . ANG II levels were assessed by RIA using a commercially available kit (EuroDiagnostica Co., Malmö, Sweden).…”
Section: Series 1: Assessment Of Systolic Bp Plasma and Kidney Ang Imentioning
confidence: 99%
“…14 Activation of the mRen2 gene is underlying the cardiovascular pathology in TGR and IHR so one would expect that IHR develop a similar form of dilated cardiomyopathy when the heart is sufficiently stressed. While myocardial hypertrophy is evident in IHR, even after short-term (<2 weeks) stimulation, 15 detailed information on cardiac function and structure is missing. A recent study reported a lack of cardiac fibrosis after prolonged mRen2 activation in IHR, but did not show data on cardiac function or heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported a lack of cardiac fibrosis after prolonged mRen2 activation in IHR, but did not show data on cardiac function or heart failure. 15 Furthermore, most studies used relatively young animals while a cardiac phenotype is usually more apparent in adult rats.…”
Section: Introductionmentioning
confidence: 99%